KAJIAN KONDISI KESEHATAN PADANG LAMUN DI PERAIRAN MOKUPA KECAMATAN TOMBARIRI KABUPATEN MINAHASA - Marthen Bongga; Calvyn F A Sondak; Deisle RH Kumampung; Kakaskasen A Roeroe; Sandra Olivia Tilaar; Joudy Sangari (JURNAL PESISIR DAN LAUT TROPIS, 2021)
Seagrass ecosystems services in the coastal waters are included as primary producers, nutrient recycler, bottom stabilizers, sediment traps, and erosion barriers. Gleaning fisheries in seagrass bed in Mokupa waters could cause damage on seagrass, that can be marked by changes in seagrass cover. The purposes of this study were to identify the types of seagrasses and to determine the health condition of seagrass bed ecosystem in Mokupa waters. The research method used in this study is quadrat transect method. Data collection was carried out by laid three transects (100 m) with distance between each transect was 50 m. A square frame (50Ã—50 cm2) which is divided into 4 squares is placed on the right side of the transect, with 10 m distance between frame. This study found four types of seagrasses, namely Enhalus acoroides, Thalassia hemprichii, Halodule pinifolia and Halophila ovalis. E. acoroides have the highest percentage cover (16.19%) followed byT. hemprichii (6.91%), H. pinifolia (4.50%) and H. ovalis (1.56%) respectively. Seagrass cover in the study area is considered medium (26-50%) while the health condition was poor (29.25%).